SECONDARY STUDENTS’ VIEWS TOWARDS THE USE OF GOOGLE CLASROOM AS AN ONLINE ASSESSMENTS TOOLS DURING COVID-19 PANDEMIC - Mia Refsi Choirunnisa; Berlinda Mandasari (Journal of Arts and Education, 2021)
Students of SMKN 1 Talangpadang have been conducting online assessment using Google Classroom during the COVID-19 pandemic. The purpose of this study is to reveal students' views towards the use of Google Classroom as an online assessments tools during covid-19 pandemic at the secondary school level. The research used a qualitative descriptive method. The data in this study were obtained from questionnaires and interviews with all X OTKP 2 students in SMKN 1 Talangpadang. The data in this study were analyzed through data condensation, data display, and conclusions. This study found that students’s views toward the use of Google Clssroom as an assessment tool during pandemic was favorable. Students view that using Google Classroom as an online assignment tool is very beneficial for students doing online assignments during the pandemic, because doing online assignments with Google Classroom is simple, practical, and flexible.